The Implementation of Deep Learning Approach in Enhancing the Quality of Learning in Elementary Schools: A Literature Review - Asmiranda Helena; Syafri Martabe Rizka Nasution; Maimunah Maimunah (Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2026)
This study aims to analyze the development, trends, and quality of scientific publications related to the Implementation of Deep Learning in Elementary Schools based on article searches on Google Scholar. This research employs a qualitative method using a library research model, in which data were obtained through searches of scientific articles using the keyword “Implementation of Deep Learning in Elementary Schools,” followed by filtering, classification, content analysis, and data presentation in the form of tables, graphs, and narrative descriptions. The results of the study show that there are 20 related articles, with a significant increase in publications in 2025. Affiliation analysis reveals that these articles originate from various regions in Indonesia, particularly West Java, Central Java, West Sumatra, and Central Sulawesi, indicating that the application of deep learning has gained national attention. Meanwhile, the journal accreditation classification indicates that 85% of the articles were published in non-accredited journals, while only a small portion were indexed in Sinta 4 and Sinta 5. Overall, this study concludes that the implementation of deep learning in elementary school learning is increasingly developing and has been proven to contribute positively to literacy, numeracy, critical thinking, discipline, and teachers’ pedagogical competence, although the quality of scientific publications still needs improvement to achieve stronger academic impact.